Management of Non Timber Forest Products (NTFPs) across the Nam Khan Watershed - Nanthavong, K.; Cherief, M.; Keophoxay, Anousith; Castella, J.C. (2011)
This study on the use of Non Timber Forest Products (NTFPs) in the Nam Khan Watershed was conducted through household surveys and focus group discussions in three villages selected along a gradient of integration to market, and diversity of livelihood systems: Houayyen and Tinpha villages in Xieng Ngeun district and Longlet village in Phonxay district, Luang Prabang province. The main objectives of this research were to assess the value and uses of NTFPs by local farmers and to compare NTFPs management strategies between accessible and remote areas. This research revealed contrasted NTFPs management strategies between accessible areas and remote areas. More NTFPs species are collected in remote areas than in accessible areas but a bigger quantity is collected in accessible areas. In the remote areas, NTFPs are mainly consumed because of poor market accessibility, while most NTFPs collected in accessible areas are sold on the market. The diversity of NTFPs species available in the landscape influences local household management less than the possibility to get access to market. As a consequence, bigger volumes of a few species are collected in accessible areas for income generation while limited volume of more diverse species are collected in remote areas for food security. In remote areas, NTFPs are primarily collected in forests and old fallows while people in accessible areas have to collect NTFPs in young fallows that are individually appropriated and on agricultural land. Some commercial species (e.g. posaa, khem, peuakmeuak) are gradually domesticated as forest and old fallow patches get smaller, fragmented and scarce in the landscape. Sustainable management about NTFPs across the Nam Khan watershed should integrate conservation – development objectives at the watershed scale by increased exchanges between upstream and downstream villages and with the emerging markets. Sustainable NTFPs management plans should be designed not only at the village level but also at higher administrative levels (e.g. kumban, district, province, watershed) to tackle both environmental and livelihood issues. Protection of wildlife and biodiversity requires a better access to formal education in remote areas and environmental awareness in accessible areas.